Field and Laboratory Evaluation of Bermudagrass Germplasm for Cold Hardiness and Freezing Tolerance. Issue 1 (1st January 2019) - Dunne, Jeffrey C.; Tuong, Tan D.; Livingston, David P.; Reynolds, W. Casey; Milla-Lewis, Susana R.
Abstract : Bermudagrass [ Cynodon spp. (L.) Rich.] is a high‐quality, durable turfgrass with excellent heat and drought tolerance. However, its lack of freezing tolerance limits its use in the transition zone. The development of cultivars with enhanced freezing tolerance would constitute a significant improvement in the management of bermudagrass in this region and could extend its area of adaptation further north. There has been substantial work on screening of common‐type bermudagrass [ Cynodon dactylon (L.) Pers.] germplasm for freezing tolerance, but not for the African ( Cynodon transvaalensis Burtt‐Davy) germplasm. The purpose of this research was to conduct multiyear field testing and laboratory‐based freezing test evaluations of winter hardiness and freezing tolerance, respectively, of an African and common bermudagrass germplasm collection. A high level of cold hardiness was observed among the germplasm in this study. In field evaluations, plant introductions (PIs) PI 290905, PI 647879, PI 255447, PI 289923, and PI 615161 were the top performers, having consistently greater spring green‐up and reduced winterkill compared with 'Patriot', 'Tifsport', 'Quickstand', and 'Tifway', though not always significantly. A comparison between field‐based ratings and calculated lethal temperatures for 50% death (LT50 ) from laboratory‐based freezing tests showed significant correlations of −0.26 and −0.24 for spring green‐up and winterkill, respectively, suggesting that these controlled freeze experiments could be used to prescreen materials prior to field testing. Overall, results indicate that some of the PIs evaluated in this study can be used as additional sources of cold hardiness in bermudagrass breeding.